Electroacupuncture for motor dysfunction and constipation in patients with Parkinson's disease: a randomised controlled multi-centre trialResearch in context - Kunshan Li; Shifen Xu; Ruiping Wang; Xuan Zou; Huirong Liu; Chunhai Fan; Jing Li; Guona Li; Yiwen Wu; Xiaopeng Ma; Yiyi Chen; Chenfang Hu; et al. (EClinicalMedicine, 2023)
Summary: Background: Motor disturbances and non-motor disturbances such as constipation are the main factors affecting the quality of life in patients with Parkinson's disease (PD). We investigated the efficacy and safety of electroacupuncture combined with conventional pharmacological treatment on motor dysfunction and constipation in PD. Methods: In this multi-centre randomised controlled trial, we enrolled 166 eligible participants between September 19, 2018 and September 25, 2019 in four hospitals in China. Participants were randomly assigned (1:1) to the electroacupuncture (EA) group and the waitlist control group. Each participant in both groups received the conventional pharmacological treatment, EA group received 3 sessions of electroacupuncture per week for 12 weeks. The primary outcome was the change in the Unified Parkinson's Disease Rating Scale (UPDRS) score from baseline to week 12. The secondary outcomes included the evaluation of functional disability in motor symptoms and constipation, the adherence and adverse events were also recorded. Registered with Chictr.org.cn, ChiCTR1800019517. Findings: At week 12, the change in the UPDRS score of the EA group was significantly higher than that of the control group, with a difference of −9.1 points (95% CI, −11.8 to −6.4), and this difference continued into weeks 16 and 24. From baseline to week 12, the 39-item Parkinson Disease Question (PDQ-39) decreased by 10 points (interquartile range, IQR −26.0 to 0.0) in the EA group and 2.5 points (IQR: −11.0 to 4.0) in the control group, the difference was statistically significant. The time and steps for the 20-m walk at week 12, as well as the changes from baseline in the EA group, were comparable with that in the control group. But the EA group had a greater decrease than the control group from baseline in the times for 20-m walks at weeks 16 and 24. From week 4 to week 24, the median values of spontaneous bowel movements (SBMs) per week in the EA group were higher than that in the control group, the differences were all statistically significant. The incidence of EA-related adverse events during treatment was low, and they are mild and transient. Interpretation: The findings of our study suggested that compared with conventional pharmacological treatment, conventional pharmacological treatment combined with electroacupuncture significantly enhances motor function and increased bowel movements in patients with PD, electroacupuncture is a safe and effective treatment for PD. Funding: Shanghai “Science and Technology Innovation Action Plan” Clinical Medicine Field Project (18401970700), Shanghai Special Project on Aging and Women's and Children's Health Research (020YJZX0134), Shanghai Clinical Research Centre for Acupuncture and Moxibustion (20MC1920500).